국소마취하에서 백내장 수술에 따른 불안정도와 항불안제 근육하 주사 및 마사지 프로그램의 불안 감소효과 비교 - 김만수; Man Soo Kim; 조경숙; Kyung Sook Cho (Daihan angwa haghoi jabji, 1999)
본 연구는 국소마취 백내장 수술환자의 불안 정도를 알아보고 현재 사용하는 항불안 약제투여(diazepam0와 새로운 불안중재요법인 손마사지가 불안감소에 미치는 효과를 파악하여, 유용한 불안 중재방법을 개발하고자 실시하였다. 1996년 12월 11일부터 1997년 2월 12일까지 백내장 수술환자 89명을 약물투여군 30명, 손마사지군 29명, 대조군 30명으로 나누어 약물투여와 손마사지를 각각 실시하여 다음과 같은 결과를 얻었다. 1. 손마사지 후 심리적 불안정도, 수축기 및 이완기 혈압, 맥박수는 마사지 전에 비해 유의하게 감소하였다. 2. 혈청 에피네프린, 노어에피네프린은 손마사지군에서 유의하게 감소하였고 코티졸치는 감소경향이었는데, 이는 약물투여군 과 대조군에 비해서는 에피네프린, 노어에피네프린 및 코티졸치 모두 유의한 차이를 보였다. 혈당치는 세 군 사이에 유의한 의미를 발견할 수 없었다. 3. 호중구와 림프구의 백분율은 세 군 모두에서 유의한 변화를 볼 수 없었지만. 손마사지군에서는 자연살해세포가 실험후 유의하게 증가하였고, 약물투여군과 대조군에서는 유의한 변화를 볼 수 없었다. 이상과 같은 결과로 국소마취 백내장 수술환자에게 실시한 손마사지 프로그램은 불안의 생리적 지표가 되는 혈압, 맥박수, 에피네프린, 노어에피테프린 및 코티졸값의 변화와 심리적 불안의 감소를 가져와 국소마취 수술환자의 불안감소에 효과가 있는 것으로 생각한다(한안지 40:383~395, 1999). This study was designed to investigate the anxiety level and compare the antianxietic effect of between hand massage program group and antianxiety drug intramuscular injection group in patients during cataract surgery. The subjects were eighty-nine patients, thirty for the control group, who were admitted at Kangnam St. Marys Hospital for cataract surgery. This study was carried out from December 11, 1996 to February 12, 1997.The levels of anxiety as measured by the Visual Analogue Scale, systolic blood pressure, diastolic blood pressure, and pulse rate were measured before and after hand massage program. Epinephrine, norepinephrine, cortisol, blood sugar levels, neutrophil and lymphocyte percentages, and natural killer cells in white blood cells also were measured before hand massage and five minutes before the end of the operation. The results were as follows : 1. After hand massage, psychological anxiety levels, systolic and diastolic blood pressure, and pulse rate decreased significantly compared with before hand massage. 2. The epinephrine and norepinephrine decreased significantly in the massage group, and epinephrine, norepinephrine, and cortisol increased in the intramuscular diazepam injection and control group, so there was a significant difference. There were no differences in blood sugar levels. 3. There were no differences in blood neutrophil and lymphocyte percentages in while blood cells among three group. However, natural killer cells in lymphocytes tended to significantly increase in the massage group. These findings indicate that hand massage program could be effective in decreasing the psychological anxiety levels in cataract surgery under local anesthesia(J Korean Ophthalmol Soc 40:383~395, 1999).